Nurses’ therapeutic communication and its correlation with family anxiety in the intensive care unit setting - Dwi Winarti, Tutik; Trigantara, Regista; Fatmawati, Diana Noor (Palembang MediRose Publisher, 2024)
Background: Patients admitted to the Intensive Care Unit (ICU) are often in critical, life-threatening conditions, which are typically sudden and unplanned. This situation can lead to significant anxiety among their family members. Therapeutic communication is one strategy used by nurses to help reduce the anxiety levels of patients’ families.Objective: This study aimed to examine the relationship between nurses’ therapeutic communication skills and the anxiety levels of patients’ family members in the ICU.Methods: A cross-sectional study was conducted using purposive sampling to select 80 participants. Data were collected using the Hamilton Anxiety Rating Scale (HARS) and a therapeutic communication questionnaire. Descriptive analysis was performed, and the Spearman Rho test was used to assess correlations, with a significance level set at ? = 0.05. Results: The findings showed that 58 respondents (72.5%) perceived nurses’ therapeutic communication as being in the “good” category, while 52 respondents (65.0%) experienced mild levels of anxiety. Statistical analysis revealed a significant relationship between therapeutic communication and the anxiety levels of patients’ family members, with a p-value of 0.001 (p < 0.05) and a correlation coefficient of r = -0.351.Conclusion: The results indicate that better therapeutic communication by nurses is associated with lower anxiety levels among family members of ICU patients. Therefore, it is recommended that nurses enhance their therapeutic communication techniques to help reduce family members’ anxiety during ICU patient care.